A kind of pink high borosilicate glass and preparation method thereof
By using modified colorants and reinforcement materials in borosilicate glass, the problem of poor volatility and colorant compatibility is solved, and the mechanical properties, color uniformity and thermal stability of the glass are improved.
Patent Information
- Application Number
- CN202510214129.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-26
AI Technical Summary
In the high-borosilicate melting process, boron atoms are easily volatile during the high-temperature melting process, affecting strength, and the poor compatibility of the colorant with the high-borosilicate glass leads to poor color development effect and weak impact resistance.
Using modified colorants and reinforcement materials, the modified colorants are formed by reacting the surface-modified erbium oxide powder with amphoteric alkali lignin and sodium zirconium silicate solution by reacting the reaction of white carbon black, glucose and citric acid to form white carbon black loaded with porous carbon, and mixed with silicate to improve the mechanical properties and color uniformity of high borosilicate glass.
Through the use of modified colorants and reinforcement materials, the mechanical properties, color uniformity and boron stability of high boron silicon glass are improved, the volatility of boron is reduced, and the impact resistance and thermal stability of the glass are enhanced.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of borosilicate glass, and in particular to pink high-borosilicate glass and a preparation method thereof. Background Art
[0002] High borosilicate glass is a special glass material with low expansion rate, high temperature resistance, high strength, high hardness, high light transmittance and high chemical stability. Due to its excellent performance, it is widely used in optics, chemical and pharmaceutical industries. With the improvement of glass melting technology and the advancement of glass forming and processing technology, colored high borosilicate glass has also attracted more and more attention, and higher requirements have been put forward for the performance of high borosilicate glass. Colored high borosilicate glass is usually made by high-temperature fusion of colorants and the raw materials of high borosilicate glass (silicon dioxide, boron oxide), so that the high borosilicate glass presents unique color and excellent performance, increasing the application range of high borosilicate glass.
[0003] Colored borosilicate glass, such as pink borosilicate glass, can emit pink light and has multiple functions such as good shading effect, good sound insulation effect, high safety, and good pink decorative effect. It is beautiful, durable, environmentally friendly and healthy, and is widely used in construction, home decoration, and artwork production. However, colorants (such as erbium oxide, etc.) have poor compatibility with borosilicate glass, resulting in poor color rendering effect. In addition, boron atoms in borosilicate glass are easily volatilized during the high-temperature melting process, which affects the strength of the borosilicate glass. In addition, the impact resistance of borosilicate glass is relatively weak, which affects the use of borosilicate glass. Summary of the invention
[0004] The present invention provides a pink high-borosilicate glass and a preparation method thereof, which solve the problems of poor coloring effect caused by poor compatibility between a colorant and high-borosilicate glass and easy volatilization of boron atoms in the high-borosilicate glass during high-temperature melting.
[0005] The technical solution of the present invention:
[0006] A pink high borosilicate glass, comprising the following raw materials in parts by weight: 60-70 parts of silicon dioxide, 10-15 parts of boron oxide, 1-3 parts of a modified colorant, 5-8 parts of a reinforcing material, 8-10 parts of sodium chloride, 2-6 parts of aluminum oxide, 3-5 parts of zinc oxide, and 5-8 parts of calcium oxide;
[0007] The modified colorant is obtained by mixing erbium oxide powder surface-modified by a silane coupling agent, and then reacting with amphoteric alkaline lignin and sodium zirconium silicate solution;
[0008] The reinforcing material is obtained by mixing white carbon black, glucose and citric acid with silicate after reaction.
[0009] A method for preparing pink high borosilicate glass comprises the following preparation steps:
[0010] S1. The silica, boron oxide, modified colorant, reinforcing material, sodium chloride, aluminum oxide, zinc oxide and calcium oxide are mixed and ball-milled for 1-3h to obtain a mixture;
[0011] S2. The mixed material is melted at 1600-1700°C for 3-5 hours to obtain a glass melt, and the glass melt is flowed into a molding mold. After annealing treatment, it is cooled to room temperature to obtain a pink high borosilicate glass.
[0012] Further, the annealing process is as follows: the temperature is lowered to 800-900°C at a rate of 4-6°C / min, kept at this temperature for 1-3 hours, and then the temperature is lowered to 350-450°C at a rate of 8-12°C / min, and kept at this temperature for 0.5-1.5 hours.
[0013] Further, the modified colorant is specifically prepared by the following steps:
[0014] A1. Add erbium oxide powder to ethanol and deionized water, stir evenly, add silane coupling agent, stir and react at 60-80 ° C for 1-2h, cool to room temperature, filter, wash and dry to obtain amino erbium oxide powder;
[0015] A2. Add lignin to deionized water, stir evenly, add sodium hydroxide solution to adjust the solution pH to 10-12, heat to 80-90 ° C, add 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir for 3-5 hours, cool to room temperature, and freeze-dry to obtain amphoteric alkaline lignin;
[0016] A3. The aminated erbium oxide powder and amphoteric alkaline lignin were added to deionized water, stirred evenly, sodium hydroxide was added, stirred and reacted at 60-70 ° C for 20-30 min, cooled to room temperature, filtered, washed, and dried to obtain amphoteric alkaline lignin modified erbium oxide powder;
[0017] A4. Add sodium zirconium silicate to deionized water, heat to 50-70°C, stir at 500-600r / min for 30-40min, and cool to room temperature to obtain a sodium zirconium silicate solution; mix the amphoteric alkaline lignin modified erbium oxide powder, sodium zirconium silicate solution and deionized water, stir evenly, heat to 50-60°C, stir and mix for 30-40min, collect the solid by filtration, and after the solid is dried, obtain a modified colorant.
[0018] Furthermore, during the above-mentioned reaction A1, the silanol groups produced by the hydrolysis of the silane coupling agent can be chemically bonded to the hydroxyl groups on the surface of the erbium oxide powder, so that the silane coupling agent is grafted onto the surface of the erbium oxide powder, providing reactive functional group amino groups for the erbium oxide powder, which is beneficial to the grafting of amphoteric alkaline lignin onto the surface of the erbium oxide powder.
[0019] Furthermore, in the above-mentioned reaction process A2, the chlorine element in 3-chloro-2-hydroxypropyltrimethylammonium chloride can react with the hydroxyl group on the lignin molecular chain to graft 3-chloro-2-hydroxypropyltrimethylammonium chloride onto the lignin molecular chain, so that the lignin carries a quaternary ammonium root cationic group, and the carboxyl and hydroxyl groups contained are anionic groups, thereby forming an amphoteric alkaline lignin with amphiphilic compounds.
[0020] Furthermore, during the above-mentioned reaction A3, the amino groups carried on the surface of the aminated erbium oxide powder can be chemically bonded to some hydroxyl groups and carboxyl groups on the amphoteric alkali lignin molecular chain, so that the amphoteric alkali lignin is grafted on the surface of the aminated erbium oxide powder to obtain an amphoteric alkali lignin-modified erbium oxide powder.
[0021] Furthermore, during the above-mentioned A4 reaction process, sodium zirconium silicate is dissolved in deionized water, so that the sodium zirconium silicate solution is rich in a large amount of silicate ions and zirconium ions. The quaternary ammonium cation groups and carboxyl and hydroxyl anion groups carried by the amphoteric alkaline lignin on the surface of the amphoteric alkaline lignin-modified erbium oxide powder can be combined with the silicate ions and zirconium ions through chemical bonds, so that the silicate ions and zirconium ions are attached to the surface of the amphoteric alkaline lignin-modified erbium oxide powder as modified colorants.
[0022] Furthermore, in step A1, the ratio of the erbium oxide powder, ethanol, deionized water and silane coupling agent is (4-6) g: (25-35) mL: (8-12) mL: (1-2) g.
[0023] Furthermore, in step A2, the ratio of the amount of lignin, deionized water and 3-chloro-2-hydroxypropyltrimethylammonium chloride is (8-12) g: (80-120) mL: (4-5) g.
[0024] Furthermore, in step A3, the ratio of the amount of the aminated erbium oxide powder, the amphoteric alkaline lignin, the deionized water and the sodium hydroxide is (5-6) g: (2-3) g: (45-55) mL: (0.3-0.7) g.
[0025] Furthermore, in step A4, the ratio of sodium zirconium silicate to deionized water is (8-12) g: (15-25) mL.
[0026] Furthermore, in step A4, the ratio of the amphoteric alkaline lignin modified erbium oxide powder, sodium zirconium silicate solution and deionized water is (4-6) g: (15-25) mL: (8-12) mL.
[0027] Furthermore, the particle size of the erbium oxide powder is 10-20 μm, Shandong Desheng New Materials Co., Ltd.
[0028] Furthermore, the silane coupling agent is γ-aminopropyltriethoxysilane.
[0029] Furthermore, the reinforcing material is specifically prepared by the following steps:
[0030] B1. Add white carbon black, glucose and citric acid to ethanol, stir evenly, add hydrochloric acid solution, stir and react at 65-75°C for 20-30min, filter, wash, dry, add potassium hydroxide solution, carbonize at 700-900°C for 2-4h, cool to room temperature, take out, wash, dry to obtain white carbon black loaded with porous carbon;
[0031] B2. Add silicate to hydrochloric acid, stir evenly, add white carbon loaded with porous carbon, continue stirring and mixing for 20-30 minutes, let stand, collect solid by filtration, wash and dry the solid to obtain a reinforced material.
[0032] Furthermore, in the above-mentioned B1 reaction process, citric acid, as a linker, can be combined with the hydroxyl groups contained on the surface of silica and the oxygen-containing functional groups in glucose through chemical bonds, so that the glucose is coated on the surface of silica and carbonized at 700-900°C. The glucose on the surface of silica is decomposed by heat to form a dense carbon layer, and the activator potassium hydroxide molecules are decomposed to form pores on the surface of the dense carbon layer, thereby realizing the synthesis of porous carbon on the surface of silica, and obtaining silica loaded with porous carbon.
[0033] Furthermore, in the above B2 reaction process, the porous carbon on the surface of the porous carbon-loaded silica has excellent adsorption properties and can adsorb silicate into the pore structure of the porous carbon-loaded silica surface to obtain a reinforced material.
[0034] Furthermore, in step B1, the amount ratio of white carbon black, glucose, citric acid, ethanol, hydrochloric acid solution and potassium hydroxide solution is (2-3) g: (3-5) g: (0.4-0.6) g: (45-55) mL: (0.4-0.6) mL: (4-6) mL.
[0035] Furthermore, in step B2, the ratio of the amount of the silicate, hydrochloric acid and the white carbon black loaded with porous carbon is (2-3) g: (15-25) mL: (4-6) g.
[0036] Furthermore, the silicate is selected from any one of barium silicate, magnesium silicate and calcium silicate.
[0037] Furthermore, the particle size of white carbon black is 70-80 μm.
[0038] The present invention has the following beneficial effects:
[0039] (1) In the technical solution of the present invention, the silane coupling agent is grafted onto the surface of the erbium oxide powder, which is conducive to grafting amphoteric alkali lignin onto the surface of the erbium oxide powder; the amphoteric alkali lignin is grafted onto the surface of the amino erbium oxide powder, and the amphoteric alkali lignin can produce an adsorption and bonding effect with the raw materials of the high borosilicate glass, thereby improving the dispersibility of the amino erbium oxide powder in the high borosilicate glass, so that the erbium oxide powder is evenly distributed in the high borosilicate glass, thereby avoiding the poor compatibility of the erbium oxide powder colorant with the high borosilicate glass, which is easy to migrate and precipitate, resulting in uneven color of the high borosilicate glass. In addition, the erbium oxide powder has excellent optical properties and is pink in color. As an additive, the high borosilicate glass showing pink can be prepared.
[0040] (2) In the technical solution of the present invention, silicate ions and zirconium ions in the sodium zirconium silicate solution are attached to the surface of the amphoteric alkaline lignin modified erbium oxide powder. On the one hand, the amphoteric alkaline lignin modified erbium oxide powder is combined with the silicate ions and zirconium ions through chemical bonds, so that the lignin on the surface of the amphoteric alkaline lignin modified erbium oxide powder undergoes a cross-linking reaction, forming a lignin cross-linked network structure on the surface of the erbium oxide powder. Then, during the high-temperature melting process of the glass, the formed lignin cross-linked network is carbonized, thereby forming a dense cross-linked carbon network structure that can be filled to a high temperature. In the borosilicate glass matrix, the colorant erbium oxide powder is tightly combined with the high borosilicate glass to avoid uneven distribution of erbium oxide powder, which leads to uneven color of the high borosilicate glass. On the other hand, the zirconium ions in the cross-linked carbon network structure can generate borates with the boric acid in the high borosilicate glass, so that the borates are embedded in the cross-linked carbon network structure, which improves the stability of boron, reduces the volatilization of boron, and enhances the strength of the high borosilicate glass. In addition, the formed cross-linked carbon network structure can absorb the stress generated by external forces and improve the mechanical properties of the high borosilicate glass.
[0041] (3) In the technical solution of the present invention, the surface of the modified colorant contains silicate ions and zirconium ions. During the high-temperature melting process of the glass, the zirconium ions will induce the boron-oxygen triangular structure in the high borosilicate glass to form a more compact boron-oxygen tetrahedron structure. The silicate ions can combine with the silicon-oxygen tetrahedron formed during the melting of the glass raw materials to form a more compact and strong three-dimensional skeleton structure. The modified colorant promotes the formation of the two dense structures, improves the binding force of the modified colorant in the high borosilicate glass, and enhances the mechanical properties of the high borosilicate glass.
[0042] (4) In the technical solution of the present invention, porous carbon is synthesized on the surface of silica. On the one hand, the porous carbon synthesized on the surface of silica has high adsorption performance and can adsorb and capture boron atoms volatilized at high temperatures, thereby reducing the volatilization of boron atoms and enhancing the strength of high borosilicate glass. On the other hand, the porous carbon and silica have low thermal conductivity, which can avoid local cracking of the high borosilicate glass caused by rapid expansion or contraction of the high borosilicate glass, thereby improving the thermal stability of the high borosilicate glass.
[0043] (5) In the technical solution of the present invention, silicate is adsorbed into the pore structure of the surface of white carbon loaded with porous carbon, the pore size is refined, the porosity is increased, and the thermal stability of the high borosilicate glass is further enhanced. The metal salt ions in the silicate can also react with the boric acid in the high borosilicate glass to form borates, so that the reinforcing material is uniformly distributed in the high borosilicate glass in the form of chemical bonds, thereby enhancing the mechanical properties of the high borosilicate glass. DETAILED DESCRIPTION
[0044] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] The raw materials used in the examples of the present invention are as follows, and all reagents used are of analytical grade.
[0046] Among them, the purity of silica is 99%, Condis Chemical (Hubei) Co., Ltd.
[0047] The purity of boron oxide is 99.5%, Liaoning Boron Technology Co., Ltd.
[0048] The particle size of erbium oxide powder is 15 μm, Shandong Desheng New Materials Co., Ltd.
[0049] The silane coupling agent is γ-aminopropyltriethoxysilane.
[0050] White carbon black is precipitated silica with a content of 99% and a particle size of 75μm.
[0051] Lignin content 99%, CAS: 9005-53-2, Wuhan Kemik Biopharmaceutical Technology Co., Ltd.
[0052] The silicate is barium silicate.
[0053] Example 1
[0054] A pink high borosilicate glass comprises the following raw materials in parts by weight: 60 parts of silicon dioxide, 10 parts of boron oxide, 1 part of a modified colorant, 5 parts of a reinforcing material, 8 parts of sodium chloride, 2 parts of aluminum oxide, 3 parts of zinc oxide, and 5 parts of calcium oxide;
[0055] A method for preparing pink high borosilicate glass comprises the following preparation steps:
[0056] S1. The silica, boron oxide, modified colorant, reinforcing material, sodium chloride, aluminum oxide, zinc oxide and calcium oxide were mixed and ball-milled for 1 h to obtain a mixture;
[0057] S2. The mixture is melted at 1600°C for 3 hours to obtain a glass melt, and the glass melt is flowed into a molding mold. After annealing, it is cooled to room temperature to obtain a pink high borosilicate glass;
[0058] The annealing process is as follows: the temperature is lowered to 800°C at a rate of 4°C / min, kept at this temperature for 1 hour, then the temperature is lowered to 350°C at a rate of 8°C / min, and kept at this temperature for 0.5 hour.
[0059] The modified colorant is specifically prepared by the following steps:
[0060] A1. 4 g of erbium oxide powder was added to 25 mL of ethanol and 8 mL of deionized water, stirred evenly, 1 g of γ-aminopropyltriethoxysilane was added, stirred and reacted at 60 ° C for 1 h, cooled to room temperature, filtered, washed 3 times with ethanol, washed 3 times with deionized water, and dried in an oven at 70 ° C for 10 min to obtain an amination erbium oxide powder;
[0061] A2. Add 8 g of lignin to 80 mL of deionized water, stir evenly, add 20% sodium hydroxide solution to adjust the solution pH to 10, heat to 80 ° C, add 4 g of 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir for 3 hours, cool to room temperature, and freeze-dry at -20 ° C for 1 hour to obtain amphoteric alkaline lignin;
[0062] A3. 5 g of amination erbium oxide powder and 2 g of amphoteric alkaline lignin were added to 45 mL of deionized water, stirred evenly, 0.3 g of sodium hydroxide was added, stirred and reacted at 60 ° C for 20 min, cooled to room temperature, filtered, washed with deionized water 3 times, and dried in an oven at 60 ° C for 10 min to obtain amphoteric alkaline lignin modified erbium oxide powder;
[0063] A4. Add 8g of sodium zirconium silicate to 15mL of deionized water, heat to 50°C, stir at 500r / min for 30min, and cool to room temperature to obtain a sodium zirconium silicate solution; mix 4g of amphoteric alkaline lignin modified erbium oxide powder, 15mL of sodium zirconium silicate solution and 8mL of deionized water, stir evenly, heat to 50°C, stir and mix for 30min, collect the solid by filtration, and dry the solid in an oven at 70°C for 10min to obtain a modified colorant.
[0064] The reinforcement material is specifically prepared by the following steps:
[0065] B1. Add 2g of white carbon black, 3g of glucose and 0.4g of citric acid to 45mL of ethanol, stir evenly, add 0.4mL of 36% hydrochloric acid solution, stir and react at 65℃ for 20min, filter, wash with deionized water 3 times, dry in an oven at 70℃ for 10min, place in a tube furnace, add 4mL of 0.1mol / L potassium hydroxide solution, carbonize at 700℃ for 2h, cool to room temperature, take out, wash with deionized water until the washing liquid is neutral, and dry in an oven at 70℃ for 10min to obtain white carbon black loaded with porous carbon;
[0066] B2. Add 2 g of barium silicate to 15 mL of 36% hydrochloric acid, stir evenly, add 4 g of porous carbon-loaded white carbon black, continue stirring and mixing for 20 minutes, let stand, collect the solid by filtration, wash the solid three times with deionized water, and dry it in an oven at 70°C for 10 minutes to obtain a reinforced material.
[0067] Example 2
[0068] A pink high borosilicate glass comprises the following raw materials in parts by weight: 65 parts of silicon dioxide, 13 parts of boron oxide, 2 parts of a modified colorant, 7 parts of a reinforcing material, 9 parts of sodium chloride, 4 parts of aluminum oxide, 4 parts of zinc oxide, and 6 parts of calcium oxide;
[0069] A method for preparing pink high borosilicate glass comprises the following preparation steps:
[0070] S1. The silica, boron oxide, modified colorant, reinforcing material, sodium chloride, aluminum oxide, zinc oxide and calcium oxide were mixed and ball-milled for 2 hours to obtain a mixture;
[0071] S2. The mixture is melted at 1650° C. for 4 hours to obtain a glass melt, and the glass melt is flowed into a molding mold. After annealing, it is cooled to room temperature to obtain a pink high borosilicate glass;
[0072] The annealing process is as follows: the temperature is lowered to 850°C at a rate of 5°C / min, kept at this temperature for 2 hours, then the temperature is lowered to 400°C at a rate of 10°C / min, and kept at this temperature for 1 hour.
[0073] The modified colorant is specifically prepared by the following steps:
[0074] A1. 5 g of erbium oxide powder was added to 30 mL of ethanol and 10 mL of deionized water, stirred evenly, 1.5 g of γ-aminopropyltriethoxysilane was added, the reaction was stirred at 70 ° C for 1.5 h, cooled to room temperature, filtered, washed 3 times with ethanol, washed 3 times with deionized water, and dried in an oven at 70 ° C for 10 min to obtain an amination of erbium oxide powder;
[0075] A2. Add 10 g of lignin to 100 mL of deionized water, stir evenly, add 20% sodium hydroxide solution to adjust the solution pH to 11, heat to 85 ° C, add 4.5 g of 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir to react for 4 hours, cool to room temperature, and freeze-dry at -20 ° C for 1 hour to obtain amphoteric alkaline lignin;
[0076] A3. 5.5 g of amination erbium oxide powder and 2.5 g of amphoteric alkaline lignin were added to 50 mL of deionized water, stirred evenly, 0.5 g of sodium hydroxide was added, stirred and reacted at 65 ° C for 25 min, cooled to room temperature, filtered, washed with deionized water three times, and dried in an oven at 60 ° C for 10 min to obtain amphoteric alkaline lignin modified erbium oxide powder;
[0077] A4. Add 10g of sodium zirconium silicate to 20mL of deionized water, heat to 60°C, stir at 550r / min for 35min, and cool to room temperature to obtain a sodium zirconium silicate solution; mix 5g of amphoteric alkaline lignin modified erbium oxide powder, 20mL of sodium zirconium silicate solution and 10mL of deionized water, stir evenly, heat to 55°C, stir and mix for 35min, collect the solid by filtration, and dry the solid in an oven at 70°C for 10min to obtain a modified colorant.
[0078] The reinforcement material is specifically prepared by the following steps:
[0079] B1. Add 2.5g of white carbon black, 4g of glucose and 0.5g of citric acid to 50mL of ethanol, stir evenly, add 0.5mL of 36% hydrochloric acid solution, stir and react at 70℃ for 25min, filter, wash with deionized water 3 times, dry in an oven at 70℃ for 10min, place in a tube furnace, add 5mL of 0.1mol / L potassium hydroxide solution, carbonize at 800℃ for 3h, cool to room temperature, take out, wash with deionized water until the washing liquid is neutral, and dry in an oven at 70℃ for 10min to obtain white carbon black loaded with porous carbon;
[0080] B2. Add 2.5 g of barium silicate to 20 mL of 36% hydrochloric acid, stir evenly, add 5 g of porous carbon-loaded white carbon black, continue stirring and mixing for 25 minutes, let stand for 1 hour, collect the solid by filtration, wash the solid three times with deionized water, and dry it in an oven at 70°C for 10 minutes to obtain a reinforced material.
[0081] Example 3
[0082] A pink high borosilicate glass comprises the following raw materials in parts by weight: 70 parts of silicon dioxide, 15 parts of boron oxide, 3 parts of a modified colorant, 8 parts of a reinforcing material, 10 parts of sodium chloride, 6 parts of aluminum oxide, 5 parts of zinc oxide, and 8 parts of calcium oxide;
[0083] A method for preparing pink high borosilicate glass comprises the following preparation steps:
[0084] S1. The silica, boron oxide, modified colorant, reinforcing material, sodium chloride, aluminum oxide, zinc oxide and calcium oxide were mixed and ball-milled for 3 hours to obtain a mixture;
[0085] S2. The mixture is melted at 1700°C for 5 hours to obtain a glass melt, and the glass melt is flowed into a molding mold. After annealing, it is cooled to room temperature to obtain a pink high borosilicate glass;
[0086] The annealing process is as follows: the temperature is lowered to 900°C at a rate of 6°C / min, kept at this temperature for 3 hours, then the temperature is lowered to 450°C at a rate of 12°C / min, and kept at this temperature for 1.5 hours.
[0087] The modified colorant is specifically prepared by the following steps:
[0088] A1. 6 g of erbium oxide powder was added to 25 mL of ethanol and 12 mL of deionized water, stirred evenly, 2 g of γ-aminopropyltriethoxysilane was added, the reaction was stirred at 80 ° C for 2 h, cooled to room temperature, filtered, washed 3 times with ethanol, washed 3 times with deionized water, and dried in an oven at 70 ° C for 10 min to obtain an amination of erbium oxide powder;
[0089] A2. Add 12 g of lignin to 120 mL of deionized water, stir evenly, add 20% sodium hydroxide solution to adjust the solution pH to 12, heat to 90 ° C, add 5 g of 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir for 5 h, cool to room temperature, and freeze-dry at -20 ° C for 1 h to obtain amphoteric alkaline lignin;
[0090] A3. 6 g of amination erbium oxide powder and 3 g of amphoteric alkaline lignin were added to 55 mL of deionized water, stirred evenly, 0.7 g of sodium hydroxide was added, stirred and reacted at 70 ° C for 30 min, cooled to room temperature, filtered, washed with deionized water 3 times, and dried in an oven at 60 ° C for 10 min to obtain amphoteric alkaline lignin modified erbium oxide powder;
[0091] A4. Add 12g of sodium zirconium silicate to 25mL of deionized water, heat to 70°C, stir at 600r / min for 40min, and cool to room temperature to obtain a sodium zirconium silicate solution; mix 6g of amphoteric alkaline lignin modified erbium oxide powder, 25mL of sodium zirconium silicate solution and 12mL of deionized water, stir evenly, heat to 60°C, stir and mix for 40min, collect the solid by filtration, and dry the solid in an oven at 70°C for 10min to obtain a modified colorant.
[0092] The reinforcement material is specifically prepared by the following steps:
[0093] B1. Add 3g of white carbon black, 5g of glucose and 0.6g of citric acid to 55mL of ethanol, stir evenly, add 0.6mL of 36% hydrochloric acid solution, stir and react at 75℃ for 30min, filter, wash with deionized water 3 times, dry in a 70℃ oven for 10min, place in a tube furnace, add 6mL of 0.1mol / L potassium hydroxide solution, carbonize at 900℃ for 4h, cool to room temperature, take out, wash with deionized water until the washing liquid is neutral, and dry in a 70℃ oven for 10min to obtain white carbon black loaded with porous carbon;
[0094] B2. Add 3 g of barium silicate to 25 mL of 36% hydrochloric acid, stir evenly, add 6 g of porous carbon-loaded white carbon black, continue stirring and mixing for 30 minutes, let stand for 1 hour, collect the solid by filtration, wash the solid three times with deionized water, and dry it in an oven at 70°C for 10 minutes to obtain a reinforced material.
[0095] Comparative Example 1
[0096] A pink high borosilicate glass comprises the following raw materials in parts by weight: 70 parts of silicon dioxide, 15 parts of boron oxide, 3 parts of a modified colorant, 8 parts of a reinforcing material, 10 parts of sodium chloride, 6 parts of aluminum oxide, 5 parts of zinc oxide, and 8 parts of calcium oxide;
[0097] A method for preparing pink high borosilicate glass comprises the following preparation steps:
[0098] S1. The silica, boron oxide, modified colorant, reinforcing material, sodium chloride, aluminum oxide, zinc oxide and calcium oxide were mixed and ball-milled for 3 hours to obtain a mixture;
[0099] S2. The mixture is melted at 1700°C for 5 hours to obtain a glass melt, and the glass melt is flowed into a molding mold. After annealing, it is cooled to room temperature to obtain a pink high borosilicate glass;
[0100] The annealing process is as follows: the temperature is lowered to 900°C at a rate of 6°C / min, kept at this temperature for 3 hours, then the temperature is lowered to 450°C at a rate of 12°C / min, and kept at this temperature for 1.5 hours.
[0101] The modified colorant is specifically prepared by the following steps:
[0102] A1. Add 12 g of lignin to 120 mL of deionized water, stir evenly, add 20% sodium hydroxide solution to adjust the pH of the solution to 12, heat to 90 ° C, add 5 g of 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir for 5 hours, cool to room temperature, and freeze-dry at -20 ° C for 1 hour to obtain amphoteric alkaline lignin;
[0103] A2. 6 g of erbium oxide powder and 3 g of amphoteric alkaline lignin were added to 55 mL of deionized water, stirred evenly, 0.7 g of sodium hydroxide was added, stirred and reacted at 70 ° C for 30 min, cooled to room temperature, filtered, washed with deionized water three times, and dried in an oven at 60 ° C for 10 min to obtain amphoteric alkaline lignin modified erbium oxide powder;
[0104] A3. Add 12g of sodium zirconium silicate to 25mL of deionized water, heat to 70°C, stir at 600r / min for 40min, and cool to room temperature to obtain a sodium zirconium silicate solution; mix 6g of amphoteric alkaline lignin modified erbium oxide powder, 25mL of sodium zirconium silicate solution and 12mL of deionized water, stir evenly, heat to 60°C, stir and mix for 40min, collect the solid by filtration, and dry the solid in an oven at 70°C for 10min to obtain a modified colorant.
[0105] The reinforcement material is specifically prepared by the following steps:
[0106] B1. Add 3g of white carbon black, 5g of glucose and 0.6g of citric acid to 55mL of ethanol, stir evenly, add 0.6mL of 36% hydrochloric acid solution, stir and react at 75℃ for 30min, filter, wash with deionized water 3 times, dry in a 70℃ oven for 10min, place in a tube furnace, add 6mL of 0.1mol / L potassium hydroxide solution, carbonize at 900℃ for 4h, cool to room temperature, take out, wash with deionized water until the washing liquid is neutral, and dry in a 70℃ oven for 10min to obtain white carbon black loaded with porous carbon;
[0107] B2. Add 3 g of barium silicate to 25 mL of 36% hydrochloric acid, stir evenly, add 6 g of porous carbon-loaded white carbon black, continue stirring and mixing for 30 minutes, let stand for 1 hour, collect the solid by filtration, wash the solid three times with deionized water, and dry it in an oven at 70°C for 10 minutes to obtain a reinforced material.
[0108] Comparative Example 2
[0109] A pink high borosilicate glass comprises the following raw materials in parts by weight: 70 parts of silicon dioxide, 15 parts of boron oxide, 3 parts of a modified colorant, 8 parts of a reinforcing material, 10 parts of sodium chloride, 6 parts of aluminum oxide, 5 parts of zinc oxide, and 8 parts of calcium oxide;
[0110] A method for preparing pink high borosilicate glass comprises the following preparation steps:
[0111] S1. The silica, boron oxide, modified colorant, reinforcing material, sodium chloride, aluminum oxide, zinc oxide and calcium oxide were mixed and ball-milled for 3 hours to obtain a mixture;
[0112] S2. The mixture is melted at 1700°C for 5 hours to obtain a glass melt, and the glass melt is flowed into a molding mold. After annealing, it is cooled to room temperature to obtain a pink high borosilicate glass;
[0113] The annealing process is as follows: the temperature is lowered to 900°C at a rate of 6°C / min, kept at this temperature for 3 hours, then the temperature is lowered to 450°C at a rate of 12°C / min, and kept at this temperature for 1.5 hours.
[0114] The modified colorant is specifically prepared by the following steps:
[0115] A1. 6 g of erbium oxide powder was added to 25 mL of ethanol and 12 mL of deionized water, stirred evenly, 2 g of γ-aminopropyltriethoxysilane was added, the reaction was stirred at 80 ° C for 2 h, cooled to room temperature, filtered, washed 3 times with ethanol, washed 3 times with deionized water, and dried in an oven at 70 ° C for 10 min to obtain an amination of erbium oxide powder;
[0116] A2. 6 g of amination erbium oxide powder and 3 g of lignin were added to 55 mL of deionized water, stirred, 0.7 g of sodium hydroxide was added, stirred at 70 ° C for 30 min, cooled to room temperature, filtered, washed with deionized water 3 times, and dried in an oven at 60 ° C for 10 min to obtain lignin-modified erbium oxide powder;
[0117] A3. Add 12g of sodium zirconium silicate to 25mL of deionized water, heat to 70°C, stir at 600r / min for 40min, and cool to room temperature to obtain a sodium zirconium silicate solution; mix 6g of lignin-modified erbium oxide powder, 25mL of sodium zirconium silicate solution and 12mL of deionized water, stir evenly, heat to 60°C, stir and mix for 40min, collect the solid by filtration, and dry the solid in an oven at 70°C for 10min to obtain a modified colorant.
[0118] The reinforcement material is specifically prepared by the following steps:
[0119] B1. Add 3g of white carbon black, 5g of glucose and 0.6g of citric acid to 55mL of ethanol, stir evenly, add 0.6mL of 36% hydrochloric acid solution, stir and react at 75℃ for 30min, filter, wash with deionized water 3 times, dry in a 70℃ oven for 10min, place in a tube furnace, add 6mL of 0.1mol / L potassium hydroxide solution, carbonize at 900℃ for 4h, cool to room temperature, take out, wash with deionized water until the washing liquid is neutral, and dry in a 70℃ oven for 10min to obtain white carbon black loaded with porous carbon;
[0120] B2. Add 3 g of barium silicate to 25 mL of 36% hydrochloric acid, stir evenly, add 6 g of porous carbon-loaded white carbon black, continue stirring and mixing for 30 minutes, let stand for 1 hour, collect the solid by filtration, wash the solid three times with deionized water, and dry it in an oven at 70°C for 10 minutes to obtain a reinforced material.
[0121] Comparative Example 3
[0122] A pink high borosilicate glass comprises the following raw materials in parts by weight: 70 parts of silicon dioxide, 15 parts of boron oxide, 3 parts of a modified colorant, 8 parts of a reinforcing material, 10 parts of sodium chloride, 6 parts of aluminum oxide, 5 parts of zinc oxide, and 8 parts of calcium oxide;
[0123] A method for preparing pink high borosilicate glass comprises the following preparation steps:
[0124] S1. The silica, boron oxide, modified colorant, reinforcing material, sodium chloride, aluminum oxide, zinc oxide and calcium oxide were mixed and ball-milled for 3 hours to obtain a mixture;
[0125] S2. The mixture is melted at 1700°C for 5 hours to obtain a glass melt, and the glass melt is flowed into a molding mold. After annealing, it is cooled to room temperature to obtain a pink high borosilicate glass;
[0126] The annealing process is as follows: the temperature is lowered to 900°C at a rate of 6°C / min, kept at this temperature for 3 hours, then the temperature is lowered to 450°C at a rate of 12°C / min, and kept at this temperature for 1.5 hours.
[0127] The modified colorant is specifically prepared by the following steps:
[0128] A1. 6 g of erbium oxide powder was added to 25 mL of ethanol and 12 mL of deionized water, stirred evenly, 2 g of γ-aminopropyltriethoxysilane was added, the reaction was stirred at 80 ° C for 2 h, cooled to room temperature, filtered, washed 3 times with ethanol, washed 3 times with deionized water, and dried in an oven at 70 ° C for 10 min to obtain an amination of erbium oxide powder;
[0129] A2. Add 12 g of lignin to 120 mL of deionized water, stir evenly, add 20% sodium hydroxide solution to adjust the solution pH to 12, heat to 90 ° C, add 5 g of 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir for 5 h, cool to room temperature, and freeze-dry at -20 ° C for 1 h to obtain amphoteric alkaline lignin;
[0130] A3. 6 g of amination erbium oxide powder and 3 g of amphoteric alkaline lignin were added to 55 mL of deionized water, stirred evenly, 0.7 g of sodium hydroxide was added, stirred and reacted at 70 ° C for 30 min, cooled to room temperature, filtered, washed with deionized water 3 times, and dried in an oven at 60 ° C for 10 min to obtain amphoteric alkaline lignin modified erbium oxide powder;
[0131] A4. Add 12g of sodium silicate to 25mL of deionized water, heat to 70°C, stir at 600r / min for 40min, and cool to room temperature to obtain a sodium zirconium silicate solution; mix 6g of amphoteric alkaline lignin modified erbium oxide powder, 25mL of sodium zirconium silicate solution and 12mL of deionized water, stir evenly, heat to 60°C, stir and mix for 40min, collect the solid by filtration, and dry the solid in an oven at 70°C for 10min to obtain a modified colorant.
[0132] The reinforcement material is specifically prepared by the following steps:
[0133] B1. Add 3g of white carbon black, 5g of glucose and 0.6g of citric acid to 55mL of ethanol, stir evenly, add 0.6mL of 36% hydrochloric acid solution, stir and react at 75℃ for 30min, filter, wash with deionized water 3 times, dry in a 70℃ oven for 10min, place in a tube furnace, add 6mL of 0.1mol / L potassium hydroxide solution, carbonize at 900℃ for 4h, cool to room temperature, take out, wash with deionized water until the washing liquid is neutral, and dry in a 70℃ oven for 10min to obtain white carbon black loaded with porous carbon;
[0134] B2. Add 3 g of barium silicate to 25 mL of 36% hydrochloric acid, stir evenly, add 6 g of porous carbon-loaded white carbon black, continue stirring and mixing for 30 minutes, let stand for 1 hour, collect the solid by filtration, wash the solid three times with deionized water, and dry it in an oven at 70°C for 10 minutes to obtain a reinforced material.
[0135] Comparative Example 4
[0136] A pink high borosilicate glass comprises the following raw materials in parts by weight: 70 parts of silicon dioxide, 15 parts of boron oxide, 3 parts of a modified colorant, 8 parts of a reinforcing material, 10 parts of sodium chloride, 6 parts of aluminum oxide, 5 parts of zinc oxide, and 8 parts of calcium oxide;
[0137] A method for preparing pink high borosilicate glass comprises the following preparation steps:
[0138] S1. The silica, boron oxide, modified colorant, reinforcing material, sodium chloride, aluminum oxide, zinc oxide and calcium oxide were mixed and ball-milled for 3 hours to obtain a mixture;
[0139] S2. The mixture is melted at 1700°C for 5 hours to obtain a glass melt, and the glass melt is flowed into a molding mold. After annealing, it is cooled to room temperature to obtain a pink high borosilicate glass;
[0140] The annealing process is as follows: the temperature is lowered to 900°C at a rate of 6°C / min, kept at this temperature for 3 hours, then the temperature is lowered to 450°C at a rate of 12°C / min, and kept at this temperature for 1.5 hours.
[0141] The modified colorant is specifically prepared by the following steps:
[0142] A1. 6 g of erbium oxide powder was added to 25 mL of ethanol and 12 mL of deionized water, stirred evenly, 2 g of γ-aminopropyltriethoxysilane was added, the reaction was stirred at 80 ° C for 2 h, cooled to room temperature, filtered, washed 3 times with ethanol, washed 3 times with deionized water, and dried in an oven at 70 ° C for 10 min to obtain an amination of erbium oxide powder;
[0143] A2. Add 12 g of lignin to 120 mL of deionized water, stir evenly, add 20% sodium hydroxide solution to adjust the solution pH to 12, heat to 90 ° C, add 5 g of 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir for 5 h, cool to room temperature, and freeze-dry at -20 ° C for 1 h to obtain amphoteric alkaline lignin;
[0144] A3. 6 g of amination erbium oxide powder and 3 g of amphoteric alkaline lignin were added to 55 mL of deionized water, stirred evenly, 0.7 g of sodium hydroxide was added, stirred and reacted at 70 ° C for 30 min, cooled to room temperature, filtered, washed with deionized water 3 times, and dried in an oven at 60 ° C for 10 min to obtain amphoteric alkaline lignin modified erbium oxide powder;
[0145] A4. Add 12g of sodium zirconium silicate to 25mL of deionized water, heat to 70°C, stir at 600r / min for 40min, and cool to room temperature to obtain a sodium zirconium silicate solution; mix 6g of amphoteric alkaline lignin modified erbium oxide powder, 25mL of sodium zirconium silicate solution and 12mL of deionized water, stir evenly, heat to 60°C, stir and mix for 40min, collect the solid by filtration, and dry the solid in an oven at 70°C for 10min to obtain a modified colorant.
[0146] The reinforcement material is specifically prepared by the following steps:
[0147] Add 3 g of barium silicate to 25 mL of 36% hydrochloric acid, stir evenly, add 6 g of white carbon black, continue stirring and mixing for 30 minutes, let stand for 1 hour, collect the solid by filtration, wash the solid with deionized water 3 times, and dry it in an oven at 70°C for 10 minutes to obtain a reinforced material.
[0148] Comparative Example 5
[0149] A pink high borosilicate glass comprises the following raw materials in parts by weight: 70 parts of silicon dioxide, 15 parts of boron oxide, 3 parts of a modified colorant, 8 parts of a reinforcing material, 10 parts of sodium chloride, 6 parts of aluminum oxide, 5 parts of zinc oxide, and 8 parts of calcium oxide;
[0150] A method for preparing pink high borosilicate glass comprises the following preparation steps:
[0151] S1. The silica, boron oxide, modified colorant, reinforcing material, sodium chloride, aluminum oxide, zinc oxide and calcium oxide were mixed and ball-milled for 3 hours to obtain a mixture;
[0152] S2. The mixture is melted at 1700°C for 5 hours to obtain a glass melt, and the glass melt is flowed into a molding mold. After annealing, it is cooled to room temperature to obtain a pink high borosilicate glass;
[0153] The annealing process is as follows: the temperature is lowered to 900°C at a rate of 6°C / min, kept at this temperature for 3 hours, then the temperature is lowered to 450°C at a rate of 12°C / min, and kept at this temperature for 1.5 hours.
[0154] The modified colorant is specifically prepared by the following steps:
[0155] A1. 6 g of erbium oxide powder was added to 25 mL of ethanol and 12 mL of deionized water, stirred evenly, 2 g of γ-aminopropyltriethoxysilane was added, the reaction was stirred at 80 ° C for 2 h, cooled to room temperature, filtered, washed 3 times with ethanol, washed 3 times with deionized water, and dried in an oven at 70 ° C for 10 min to obtain an amination of erbium oxide powder;
[0156] A2. Add 12 g of lignin to 120 mL of deionized water, stir evenly, add 20% sodium hydroxide solution to adjust the solution pH to 12, heat to 90 ° C, add 5 g of 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir for 5 h, cool to room temperature, and freeze-dry at -20 ° C for 1 h to obtain amphoteric alkaline lignin;
[0157] A3. 6 g of amination erbium oxide powder and 3 g of amphoteric alkaline lignin were added to 55 mL of deionized water, stirred evenly, 0.7 g of sodium hydroxide was added, stirred and reacted at 70 ° C for 30 min, cooled to room temperature, filtered, washed with deionized water 3 times, and dried in an oven at 60 ° C for 10 min to obtain amphoteric alkaline lignin modified erbium oxide powder;
[0158] A4. Add 12g of sodium zirconium silicate to 25mL of deionized water, heat to 70°C, stir at 600r / min for 40min, and cool to room temperature to obtain a sodium zirconium silicate solution; mix 6g of amphoteric alkaline lignin modified erbium oxide powder, 25mL of sodium zirconium silicate solution and 12mL of deionized water, stir evenly, heat to 60°C, stir and mix for 40min, collect the solid by filtration, and dry the solid in an oven at 70°C for 10min to obtain a modified colorant.
[0159] The reinforcement material is specifically prepared by the following steps:
[0160] B1. Add 3g of white carbon black, 5g of glucose and 0.6g of citric acid to 55mL of ethanol, stir evenly, add 0.6mL of 36% hydrochloric acid solution, stir and react at 75℃ for 30min, filter, wash with deionized water 3 times, dry in a 70℃ oven for 10min, place in a tube furnace, add 6mL of 0.1mol / L potassium hydroxide solution, carbonize at 900℃ for 4h, cool to room temperature, take out, wash with deionized water until the washing liquid is neutral, and dry in a 70℃ oven for 10min to obtain white carbon black loaded with porous carbon;
[0161] B2. Add 3 g of sodium silicate to 25 mL of 36% hydrochloric acid, stir evenly, add 6 g of porous carbon-loaded white carbon black, continue stirring and mixing for 30 minutes, let stand for 1 hour, collect the solid by filtration, wash the solid three times with deionized water, and dry it in an oven at 70°C for 10 minutes to obtain a reinforced material.
[0162] The performance of the pink high borosilicate glass prepared in Examples 1-3 and Comparative Examples 1-5 is now tested.
[0163] The pink high borosilicate glass prepared above was used to prepare a glass sample with a length of 120 mm, a width of 20 mm, and a thickness of 5 mm;
[0164] Mechanical properties testing: According to the bending strength test method of glass materials published in "JC / T676-1997", a bending test was carried out on a testing machine, and the bending strength of the high borosilicate glass sample was obtained by calculating the maximum complete stress at the cross section under load; the shear modulus and elastic modulus of the high borosilicate glass prepared above were tested according to GB / T 37780-2019 standard;
[0165] Determine the boron content and the boron volatility according to GBZ / T 160.27-2004;
[0166] Glass color evaluation: Observe whether the color of the pink high borosilicate glass prepared above is uniform, without any color difference or mixed colors;
[0167] The test results are shown in Table 1 below.
[0168] Table 1 Mechanical properties test of pink high borosilicate glass prepared in Examples 1-3 and Comparative Examples 1-5
[0169]
[0170] Table 2 Color, boron volatility and linear thermal expansion coefficient performance test of pink high borosilicate glass prepared in Examples 1-3 and Comparative Examples 1-5
[0171]
[0172] It can be seen from the data in Table 1 and Table 2 that the pink high borosilicate glass prepared in Examples 1-3 has higher mechanical properties and heat resistance, and the pink colorant presents a uniform color in the glass.
[0173] In Comparative Example 1, the modified colorant prepared by replacing the amino erbium oxide powder with erbium oxide powder was added to the pink borosilicate glass. Its mechanical properties decreased and the color distribution was uneven, which proved that the silane coupling agent was grafted on the surface of the erbium oxide powder, which improved the dispersibility of the amino erbium oxide powder in the borosilicate glass and avoided the uneven color. It was also beneficial to graft amphoteric alkaline lignin on the surface of the erbium oxide powder, provide a cross-linked carbon network structure, and improve the mechanical properties of the borosilicate glass.
[0174] In Comparative Example 2, the modified colorant prepared by replacing the amphoteric alkaline lignin with lignin was added to the pink high borosilicate glass, and its mechanical properties decreased and the color distribution was uneven, proving that the amphoteric alkaline lignin can combine with the silicate ions through chemical bonds to form a dense cross-linked carbon network structure on the surface of the erbium oxide powder and fill it into the high borosilicate glass matrix to avoid the uneven distribution of the erbium oxide powder; and the silicate ions combine with the silicon-oxygen tetrahedron to form a denser and firmer three-dimensional skeleton structure, which improves the binding force of the modified colorant in the high borosilicate glass and enhances the mechanical properties of the high borosilicate glass.
[0175] In Comparative Example 3, a modified colorant prepared by replacing sodium zirconium silicate with sodium silicate was added to the pink high borosilicate glass. Its mechanical properties decreased, the boron volatilization rate increased, and the color distribution was uneven, proving that zirconium ions and amphoteric alkaline lignin are combined through chemical bonds to form a dense cross-linked carbon network structure on the surface of erbium oxide powder and filled into the high borosilicate glass matrix. In addition, zirconium ions induce the boron-oxygen triangular structure in the high borosilicate glass to form a denser boron-oxygen tetrahedral structure, thereby improving the binding force of the modified colorant in the high borosilicate glass and enhancing the mechanical properties of the high borosilicate glass.
[0176] In Comparative Example 4, the silica loaded with porous carbon is replaced with a reinforcing material prepared from silica and added to the pink high-borosilicate glass. Its mechanical properties and heat resistance decrease, and the boron volatilization rate increases. This proves that the porous carbon synthesized on the surface of silica can adsorb and capture boron atoms that volatilize at high temperatures, thereby reducing the volatilization of boron atoms and enhancing the strength of the high-borosilicate glass. In addition, the porous carbon has a lower thermal conductivity, which improves the thermal stability of the high-borosilicate glass.
[0177] In Comparative Example 5, a reinforcing material prepared by replacing barium silicate with sodium silicate is added to the pink high-borosilicate glass. The boron volatilization rate increases and the mechanical properties decrease, proving that the metal salt ions in the silicate can also react with the boric acid in the high-borosilicate glass to form borates, so that the reinforcing material is uniformly distributed in the high-borosilicate glass in the form of chemical bonds, thereby enhancing the mechanical properties of the high-borosilicate glass.
[0178] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0179] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways. As long as they do not deviate from the scope defined by the invention, they shall all fall within the protection scope of the present invention.
Claims
1. A pink high borosilicate glass, characterized in that: The invention comprises the following raw materials in parts by weight: 60-70 parts of silicon dioxide, 10-15 parts of boron oxide, 1-3 parts of modified colorant, 5-8 parts of reinforcing material, 8-10 parts of sodium chloride, 2-6 parts of aluminum oxide, 3-5 parts of zinc oxide and 5-8 parts of calcium oxide; The modified colorant is obtained by mixing erbium oxide powder surface-modified by a silane coupling agent, and then reacting with amphoteric alkaline lignin and sodium zirconium silicate solution; The silane coupling agent is γ-aminopropyltriethoxysilane; The reinforcing material is obtained by mixing white carbon black, glucose and citric acid and then mixing with silicate; The reinforcing material is specifically prepared by the following steps: B1. Add white carbon black, glucose and citric acid to ethanol, stir evenly, add hydrochloric acid solution, stir and react at 65-75°C for 20-30min, filter, wash, dry, add potassium hydroxide solution, carbonize at 700-900°C for 2-4h, cool to room temperature, take out, wash, dry to obtain white carbon black loaded with porous carbon; B2. Add silicate to hydrochloric acid, stir evenly, add white carbon loaded with porous carbon, continue stirring and mixing for 20-30 minutes, let stand, collect solid by filtration, wash and dry the solid to obtain a reinforced material.
2. The pink high borosilicate glass according to claim 1, characterized in that: The modified colorant is specifically prepared by the following steps: A1. Add erbium oxide powder to ethanol and deionized water, stir evenly, add silane coupling agent, stir and react at 60-80 ° C for 1-2h, cool to room temperature, filter, wash and dry to obtain amino erbium oxide powder; A2. Add lignin to deionized water, stir evenly, add sodium hydroxide solution to adjust the solution pH to 10-12, heat to 80-90 ° C, add 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir for 3-5 hours, cool to room temperature, and freeze-dry to obtain amphoteric alkaline lignin; A3. The aminated erbium oxide powder and amphoteric alkaline lignin were added to deionized water, stirred evenly, sodium hydroxide was added, stirred and reacted at 60-70 ° C for 20-30 min, cooled to room temperature, filtered, washed, and dried to obtain amphoteric alkaline lignin modified erbium oxide powder; A4. Add sodium zirconium silicate to deionized water, heat to 50-70°C, stir at 500-600r / min for 30-40min, and cool to room temperature to obtain a sodium zirconium silicate solution; mix the amphoteric alkaline lignin modified erbium oxide powder, sodium zirconium silicate solution and deionized water, stir evenly, heat to 50-60°C, stir and mix for 30-40min, collect the solid by filtration, and after the solid is dried, obtain a modified colorant.
3. The pink high borosilicate glass according to claim 2, characterized in that: In step A1, the amount ratio of the erbium oxide powder, ethanol, deionized water and silane coupling agent is (4-6) g: (25-35) mL: (8-12) mL: (1-2) g.
4. The pink high borosilicate glass according to claim 2, characterized in that: In step A2, the ratio of the amount of lignin, deionized water and 3-chloro-2-hydroxypropyltrimethylammonium chloride is (8-12) g: (80-120) mL: (4-5) g.
5. The pink high borosilicate glass according to claim 2, characterized in that: In step A3, the ratio of the aminated erbium oxide powder, amphoteric alkaline lignin, deionized water and sodium hydroxide is (5-6) g: (2-3) g: (45-55) mL: (0.3-0.7) g.
6. The pink high borosilicate glass according to claim 2, characterized in that: In step A4, the ratio of sodium zirconium silicate to deionized water is (8-12) g: (15-25) mL; The dosage ratio of the amphoteric alkaline lignin modified erbium oxide powder, sodium zirconium silicate solution and deionized water is (4-6) g: (15-25) mL: (8-12) mL.
7. The pink high borosilicate glass according to claim 1, characterized in that: In step B1, the amount ratio of white carbon black, glucose, citric acid, ethanol, hydrochloric acid solution and potassium hydroxide solution is (2-3) g: (3-5) g: (0.4-0.6) g: (45-55) mL: (0.4-0.6) mL: (4-6) mL.
8. The pink high borosilicate glass according to claim 1, characterized in that: In step B2, the ratio of the silicate, hydrochloric acid and white carbon black loaded with porous carbon is (2-3) g: (15-25) mL: (4-6) g.
9. A method for preparing pink high borosilicate glass according to any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: S1. The silica, boron oxide, modified colorant, reinforcing material, sodium chloride, aluminum oxide, zinc oxide and calcium oxide are mixed and ball-milled for 1-3h to obtain a mixture; S2. The mixed material is melted at 1600-1700°C for 3-5 hours to obtain a glass melt, and the glass melt is flowed into a molding mold. After annealing treatment, it is cooled to room temperature to obtain a pink high borosilicate glass.
Citation Information
Patent Citations
High-strength microcrystalline glass containing rare earth element components and preparation method of high-strength microcrystalline glass
CN106746682A
Borate silicate aluminate glass bead, and preparation method thereof
CN106865992A